Total HIV/AIDS expenditures in Dehong Prefecture, Yunnan province in 2010: the first systematic evaluation of both health and non-health related HIV/AIDS expenditures in China. - Shan, Duo; Sun, Jiangping; Yakusik, Anna; Chen, Zhongdan; Yuan, Jianhua; Li, Tao; Fu, Jeannia; Khoshnood, Kaveh; Yang, Xing; Wei, Mei; Duan, Song; Bulterys, Marc; et al. (PloS one, 2013)
We assessed HIV/AIDS expenditures in Dehong Prefecture, Yunnan Province, one of the highest prevalence regions in China, and describe funding sources and spending for different categories of HIV-related interventions and at-risk populations.
Keywords: Acquired Immunodeficiency Syndrome; China; Communicable Disease Control; Female; Health Expenditures; Humans; Male; Prevalence; Risk